Otolith size-total length relationship in spiny eel, Mastacembelus mastacembelus (Banks & Solander, 1794) inhabiting in Karakaya Dam Lake (Malatya, Turkey) - Eroglu, Mücahıt; Şen, Dursun (My University, 2009)
In this study, the relationships between total length and sagittal otolith size of a total 187 specimens belonging to the Mastacembelus mastacembelus (Banks & Solander, 1794) fish species inhabiting Karakaya Dam Lake were examined. The otolith lengths and widths were ranged between 1.44-3.82 mm and 0.8-1.71 mm, respectively. However, otolith weights were determined between 0.0003-0.0038 g. There was a stronger and positive linear relationship between the otolith size (length, width and weight) and total lengths.
Keywords: Turkey; Malatya; Mastacembelus; morphology; Karakaya Dam Lake; morphometrics; body length; body measurements; lakes; ears